Introduction of construction planning with building information modeling (BIM) technology systems at SMK 26 Jakarta - Parwadi Moengin; Ryan Faza Prasetyo; Wahyu Sejati; Feby Kartika Sari; Dhanu Setyo Bekti (Universitas Muhammadiyah Magelang, 2024)
The construction industry is undergoing significant transformation in the era of globalization and technological advancements, particularly with the implementation of Building Information Modeling (BIM) systems. Accelerating the implementation of BIM in Indonesia requires collaboration among various parties, including academia, practitioners, and institutions. Therefore, it is crucial for students to learn about BIM to prepare a competent and adaptable workforce for the future development of construction technology. The aim of this activity is to enhance understanding of the importance of introducing construction planning with BIM technology systems to students at SMK Negeri 26 Jakarta, in preparation for them to become ready-to-use workforce in the construction industry, which is increasingly oriented towards information technology. The implementation method involves delivering material sessions followed by questionnaire sessions to assess the level of understanding among students. The results of this activity indicate that 26 students (53.1%) are very proficient in this subject, 19 students (38.8%) are categorized as proficient, and 4 students (8.2%) are categorized as adequately proficient.